Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Suppose X has an exponential distribution with mean equal to 11. Determine the following: (a) (Round your answer to 3 decimal places.) (b) (Round your answer to 3 decimal places.) (c) (Round your answer to 3 decimal places.) (d) Find the value of x such that . (Round your answer to 2 decimal places.)

Sagot :

Answer:

[tex]P(X > 11) = 0.368[/tex]

[tex]P(X > 22) = 0.135[/tex]

[tex]P(X > 33) = 0.050[/tex]

[tex]x = 33[/tex]

Step-by-step explanation:

Given

[tex]E(x) = 11[/tex] --- Mean

Required (Missing from  the question)

[tex](a)\ P(X>11)[/tex]

[tex](b)\ P(X>22)[/tex]

[tex](c)\ P(X>33)[/tex]

(d) x such that [tex]P(X <x)=0.95[/tex]

In an exponential distribution:

[tex]f(x) = \lambda e^{-\lambda x}, x \ge 0[/tex] --- the pdf

[tex]F(x) = 1 - e^{-\lambda x}, x \ge 0[/tex] --- the cdf

[tex]P(X > x) = 1 - F(x)[/tex]

In the above equations:

[tex]\lambda = \frac{1}{E(x)}[/tex]

Substitute 11 for E(x)

[tex]\lambda = \frac{1}{11}[/tex]

Now, we solve (a) to (d) as follows:

Solving (a): P(X>11)

[tex]P(X > 11) = 1 - F(11)[/tex]

Substitute 11 for x in [tex]F(x) = 1 - e^{-\lambda x}[/tex]

[tex]P(X > 11) = 1 - (1 - e^{-\frac{1}{11}* 11})[/tex]

[tex]P(X > 11) = 1 - (1 - e^{-\frac{11}{11}})[/tex]

[tex]P(X > 11) = 1 - (1 - e^{-1})[/tex]

Remove bracket

[tex]P(X > 11) = 1 - 1 + e^{-1}[/tex]

[tex]P(X > 11) = e^{-1}[/tex]

[tex]P(X > 11) = 0.368[/tex]

Solving (b): P(X>22)

[tex]P(X > 22) = 1 - F(22)[/tex]

Substitute 22 for x in [tex]F(x) = 1 - e^{-\lambda x}[/tex]

[tex]P(X > 22) = 1 - (1 - e^{-\frac{1}{11}* 22})[/tex]

[tex]P(X > 22) = 1 - (1 - e^{-\frac{22}{11}})[/tex]

[tex]P(X > 22) = 1 - (1 - e^{-2})[/tex]

Remove bracket

[tex]P(X > 22) = 1 - 1 + e^{-2}[/tex]

[tex]P(X > 22) = e^{-2}[/tex]

[tex]P(X > 22) = 0.135[/tex]

Solving (c): P(X>33)

[tex]P(X > 33) = 1 - F(33)[/tex]

Substitute 33 for x in [tex]F(x) = 1 - e^{-\lambda x}[/tex]

[tex]P(X > 33) = 1 - (1 - e^{-\frac{1}{11}* 33})[/tex]

[tex]P(X > 33) = 1 - (1 - e^{-\frac{33}{11}})[/tex]

[tex]P(X > 33) = 1 - (1 - e^{-3})[/tex]

Remove bracket

[tex]P(X > 33) = 1 - 1 + e^{-3}[/tex]

[tex]P(X > 33) = e^{-3}[/tex]

[tex]P(X > 33) = 0.050[/tex]

Solving (d): x when [tex]P(X <x)=0.95[/tex]

Here, we make use of:

[tex]P(X<x) = F(x)[/tex]

Substitute [tex]F(x) = 1 - e^{-\lambda x}[/tex]

[tex]P(X<x) = 1 - e^{-\lambda x}[/tex]

So, we have:

[tex]0.95 = 1 - e^{-\lambda x}[/tex]

Subtract 1 from both sides

[tex]0.95 -1= 1-1 - e^{-\lambda x}[/tex]

[tex]-0.05=- e^{-\lambda x}[/tex]

Reorder the equation

[tex]e^{-\lambda x} = 0.05[/tex]

Substitute 1/11 for [tex]\lambda[/tex]

[tex]e^{-\frac{1}{11} x} = 0.05[/tex]

Solve for x:

[tex]x = -\frac{1}{1/11}\ ln(0.05)[/tex]

[tex]x = -11\ ln(0.05)[/tex]

[tex]x = 32.9530550091[/tex]

[tex]x = 33[/tex] --- approximated